Cauchy problem for matrix factorizations of the Helmholtz equation - Zhuraev, D. A. (Ukrains’kyi Matematychnyi Zhurnal, 2017)
We study the Cauchy problem for a system of elliptic equations of the first order with constant coefficients factorizing the Helmholtz operator in a two-dimensional bounded domain. An approximate solution of this problem based on the method of Carleman matrix is constructed.